Impact of Devaluation on Sudan’s Current Account: An Econometric Approach - Elhassan, Mohieldin Ali Mohieldin; Eldaw, Kamal Eldin Hassan Ibrahim; Yousif, Ghadda Mohamed Awad; Osman, Awad Mohamed; Elmonshid, Lena Bedawi ELFadli; Ali, Safiat Ali Saber; Hapallah, Safia Omer; Abdalla, Saadaby Mohammed Ali Dafaalla; Mahmoud, Abdalla S.; Eltahir, Yassin (Migration Letters, 2023)
This paper attempt to assess the impact of the short and long run of devaluation on domestic currency on Sudan’s current account over the period (1986 – 2020). With this objective, the autoregressive distributed lag (ARDL) cointegration test is employed to test the long run relationship hypothesis for the export and import demand functions, in addition to export price and import price functions. The cointegration test suggested that the variables in the construction of these functions are cointegrated in the long run. The associated error correction term was significant for all functions confirming the existence of long run relationship. The results indicate that devaluation, beside not improving the current account in both short and long run, in some cases, it even had a negative effect.